Traffic-related impacts on air quality around student housing in Malang, Indonesia - Muhammad Evan Wahyudi Putra; Ridwan Muhamad Rifai; Mohammad Palwa Priya Rajendra (Sustinere: Journal of Environment and Sustainability, 2026)
Urban air pollution from traffic emissions poses a significant risk to students residing in student communal housing (SCH) near major roadways. This study investigates the impact of peak hour traffic on ambient air quality around SCH in Malang City, focusing on carbon dioxide (CO₂), total volatile organic compounds (TVOC), and fine particulate matter (PM2.5). Measurements were taken at 40 SCH locations during both daytime and nighttime peak hours. The study employed Geographic Information Systems (GIS) for spatial modelling to visualise pollutant distribution and used linear regression to develop a distance recommendation model. The results revealed a strong correlation between CO₂ and TVOC concentrations and traffic volume, whereas PM2.5 levels were more influenced by atmospheric conditions. The air quality index (AQI) classification indicated a shift toward "moderate" pollution levels during the night, particularly in dense urban areas. Indicative empirical regression modelling suggested setback distances of approximately 280 m for PM2.5 and 1,500 m for CO₂. In comparison, an anomalous result of 9,000 m for TVOC highlights significant modelling uncertainty, likely caused by confounding non-traffic sources. Despite its limitations and the need for further validation, this study contributes valuable, policy-relevant insights for urban planning, especially concerning SCH or resident zoning. The findings underscore the necessity of considering both emission intensity and microclimatic factors in residential planning near major roads.